The reality of human resource training in the Directorate of Education in the Governorate of Al-Wusta in the Sultanate of Oman from the perspective of employees - Al-Junaibi, Mansoor Abdullah Salim (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the reality of human resources training in the Directorate of Education and Higher Education in Al-Wusta Governorate in Sultanate of Oman from the employees’ point of view. The researcher adopted the descriptive analytical approach, and a questionnaire was used as a tool to collect information. It was distributed to a sample of 100 employees in the directorate, representing the original community as a whole. Through statistical analysis and data processing, the results showed that the reality of human resources training in the Directorate of Education and Higher Education in Al-Wusta Governorate received an overall average of 4.03 out of 5, which is a high level. At the level of the main areas, implementation and methods came first with an average of 4.13, followed by management support and commitment (4.06), thirdly planning (4.04), and finally follow-up and evaluation (3.90), all of which were rated as high. Also, 96% of the employees in the Directorate General of Education and Higher Education in Al-Wusta Governorate received training, of which 60% received more than three training programs, and 36% received between 1-3 programs, while only 4% did not receive any training program. There were no statistically significant differences at the significance level of 0.05 in the responses of human resources according to the variables (gender, academic qualification, specialization, number of years of experience, number of training programs). The study recommends the necessity of linking training programs to what provides human resources with the ability to apply governance principles in the directorate, to pay attention to training evaluation after training and to follow up trainees through performance reports to know the extent of their benefit from training, to develop training centers, and to grant them administrative and financial autonomy.